The corrosion resistance effect of nanocomposites containing AuNPs coated onto titanium surfaces - Yeniyol, Sinem; Mutlu, Ilven; Dizman, H. Mirac; Arsu, Nergis (YILDIZ TECHNICAL UNIV, 2025)
The purpose of this work was to evaluate the corrosion of commercially pure titanium (cpTi) and polymeric AuNPs nanocomposite thin film coatings on cpTi in vitro in artificial saliva by using different electrochemical tests and surface analysis techniques. Electrochemical impedance spectroscopy (EIS), open circuit potential (OCP) and inductively coupled plasma mass spectrometry (ICP-MS) were associated with FESEM for surface characterization. OCP tests revealed higher potential values for AuNPs-Coated surfaces. Increase of the corrosion resistance for AuNPs-Coated surface was presented by EIS in artificial saliva. Average size of 20 - 30 nm AuNPs in spherical morphology forming agglomerations were observed on AuNPs-Coated surfaces. Compared to cpTi surfaces, a lower release tendency of Ti ions from the AuNPs-Coated Ti surfaces after immersion into artificial saliva was confirmed by ICPMS. Results suggest that AuNPs-Coated Ti surfaces exhibit an enhanced corrosion resistance.
Keywords: AuNPs; Corrosion; Dental implants; Metal ion release; Polymeric nanocomposites; PHOTOCHEMICAL-SYNTHESIS; PARTICLES; IMPLANTS; BEHAVIOR; Engineering